STRUCTURAL ANALYZING IN GEAR BOX COVER USING NX-NASTRAN - Nithyanandhan.T, Kannakumar.R Suresh Kumar.P (International Journal of Research Science and Management, 2014)
At first we used prototype model to analyze the component performance under varying load condition. Before manufacturing we found the capacity of component with the help of prototype. But it had some demerits like as more lead-time and redesign cost. Due to this we introduce new analyzing tools Nx-Nastran and Ansys. Here we selected Nx-Nastran to analyze the gear box cover. NX Nastran is a powerful, general purpose Finite Element Analysis (FEA) tool with an integrated graphical user interface and model, which is used to analyze linear and nonlinear stress, dynamics, and heat transfer characteristics of structures and mechanical components. It represents the latest in FEA technology with some of the fastest solvers on the market along with accurate solutions that have been trusted for over 20 years by companies in all industries. NX Nastran is available on a wide variety of platforms including 32-bit and 64-bit Windows and Linux operating systems. NX Nastran (NASA Structural analysis) is a series of commercial software products originally developed under a NASA contract in the late 1960s by MSC Software Corporation using FORTRAN programming language. It uses the Finite Element Method which discritizes geometry into small elements and solves large sparse matrices using linear algebra to find quantities like displacement and stress in order to design structures. It became the industry standard program in part due to MSC buying competitors and in corporating their advances into their products. After an antitrust settlement with the FTC in 2002, their source code was released to various organizations. Alternative Nastran versions were soon created including NEi-Nastran and NX Nastran.